Anesthesia is a potent determinant of ultra-high dose rate sparing in the murine total abdominal irradiation model - Tavakkoli, Armin D.; Daley, William W.; Hunter, David I; Allen, Beverly A.; Carpenter, Gretchen C.; Gladstone, David J.; Pogue, Brian W.; Hoopes, P. Jack (Frontiers in Oncology, 2025)
IntroductionRadiation therapy is a mainstay of treatment for numerous gastrointestinal (GI) malignancies, where our ability to deliver dose to tumors is limited by acute GI toxicity. Ultra-high dose-rate (UHDR) ‘FLASH’ irradiation can spare normal tissue, yet its dependence on physiological variables remains incompletely defined.MethodsWe compared FLASH and conventional dose-rate (CDR) 9 MeV electron total abdominal irradiation (TAI) in C57BL/6 mice anesthetized with either intraperitoneal ketamine/xylazine or inhaled isoflurane in room air, deliberately omitting supplemental oxygen. Single doses of 14 or 16 Gy were delivered, and normal-tissue injury was quantified by time-to-25% body-weight loss.ResultsAt 14 Gy, UHDR under K/X produced a marked survival advantage: by day 14, 80% of animals had not reached the weight-loss endpoint versus 40% after CDR K/X; no FLASH benefit was discernible with ISO anesthesia. Raising the dose to 16 Gy accentuated these trends; 40% of UHDR K/X mice were still below the endpoint at study termination, whereas all CDR K/X mice met it by day 7. Again, ISO abolished sparing at both dose rates. To probe mechanism, intraperitoneal oxygen tension was measured with an optical reporter in six mice. ISO anesthesia yielded significantly higher pO2 (62 ± 4 mmHg) than K/X (26 ± 10mmHg), a 2.5-fold difference.DiscussionThese findings identify anesthetic-dependent oxygenation as a reproducible confounder in pre-clinical FLASH studies: elevated pO2 under ISO negates abdominal sparing, whereas K/X preserves it across two clinically relevant doses. Rigorous control and reporting of factors that alter tissue oxygenation are therefore essential when designing experiments and, ultimately, translating FLASH radiotherapy.